2015
DOI: 10.36834/cmej.36584
|View full text |Cite
|
Sign up to set email alerts
|

Ethics education for pediatric residents: a review of the literature

Abstract: Background: Ethics education and research on medical residents is needed because, unlike medical students or experienced doctors, medical residents have to perform multiple roles simultaneously – student, teacher and clinician – thus exposing them to unique ethical stressors.  In this paper we reviewed the literature concerning ethics education in postgraduate pediatrics training programs.  Our goal was not to simply describe educational strategies and programs, but also to explore measurements and experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In addition, residents of pediatrics with multiple roles in their career as educators, students and clinicians, studentship, and clinician face particular moral challenges (10). Residents often encounter additional challenges compared to the other disciplines because of having to deal with patients, who are receiving healthcare services as well as their families (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, residents of pediatrics with multiple roles in their career as educators, students and clinicians, studentship, and clinician face particular moral challenges (10). Residents often encounter additional challenges compared to the other disciplines because of having to deal with patients, who are receiving healthcare services as well as their families (11).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study conducted in Iran demonstrated that major clinical challenges, from the view point of medical students, were rooted in not respecting the patient's autonomy (1). Clinically-related ethical issues are not included in current training programs for pediatrics residents (10).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the assessment provided time for preceptors and residents to discuss ethical decision making, which can often be lacking in resident training. 17 The OSCE can be used with junior and senior pediatric residents at any level of ethical reasoning training and professionalism skills development. The scenarios are designed to provide decision points to residents.…”
Section: Discussionmentioning
confidence: 99%
“…Ethics educators in pediatrics and surgical residencies have similarly advocated the use of small-group discussions based on real-life clinical cases drawn from residents' own clinical experience. 35,36 Focusing discussions on real scenarios from residents' experience importantly allows residents to debrief, reflect upon, and emotionally process difficult cases that they have struggled with as trainees and junior clinicians, which may help prevent burnout. Residents express high levels of satisfaction with such debriefings, and find them to be a source of emotional and social support.…”
Section: New Modalities In Medical Ethics Educationmentioning
confidence: 99%